Policies to Promote Cereal Intensification in Ethiopia: The Search for Appropriate Public and Private Roles - Spielman, David J.; Byerlee, Derek; Alemu, Dawit; Kelemework, Dawit (2012)
Over the past decade, policymakers have been searching for an appropriate blend of public and private sector roles to accelerate the intensification of food staple production, smallholder commercialization, and sustainable market development in sub-Saharan Africa. In Ethiopia, steps taken to liberalize markets in the 1990s and promote fertilizer and seed packages have yet to generate payoffs in terms of higher cereal yields, lower food prices, or reduced dependency on food aid. This raises concern about the performance of the agricultural sector, specifically in terms of the systems for providing improved seed, fertilizer, credit, and extension services. This paper examines the evolving roles of the public and private sectors in intensifying cereal production in Ethiopia. Findings suggest that while Ethiopia has an admirable record of supporting agriculture, its state-led policies has now outlived their usefulness. These findings for Ethiopia offer lessons that are potentially applicable to other sub-Saharan African countries facing similar challenges.